Transcriptome analysis highlights the role of ferroptosis in palmitic acid–induced endothelial dysfunction. Issue 1 (24th January 2023) - Tan, Xiao-Hui; Gu, Yang-Yang; Song, Wen-Peng; Nan, Tie-Gui; Song, Wei-Dong; Fang, Dong; Yuan, Yi-Ming; Xin, Zhong-Cheng; Li, Xue-Song; Guan, Rui-Li
Abstract: Background: Palmitic acid (PA) has a lipotoxic effect on blood vessels, leading to endothelial dysfunction and cell death. The underlying mechanisms are not yet fully understood. Aim: We sought to investigate the effects of PA on endothelial cells, with an emphasis on ferroptosis. Methods: Rat corpus cavernosum endothelial cells (RCCECs) and human umbilical vein endothelial cells (HUVECs) were treated with PA to induce a pattern of cell death, as evidenced by the evaluation of cell viability. The differentially expressed genes were measured via RNA sequencing to reveal potential mechanisms. The intracellular levels of glutathione (GSH), malondialdehyde (MDA), ferrous ion (Fe 2+ ), and reactive oxygen species (ROS) were evaluated using commercial kits. Western blot was performed to determine the expressions of relative proteins. Outcomes: At the end of the study period, the evaluated outcomes were cell viability, transcriptome profiles, the expressions of glutathione peroxidase 4 (GPX4) and solute carrier family 7 member 11 (SLC7A11), as well as levels of GSH, MDA, Fe 2+, and ROS. Results: PA-induced cell death of RCCECs and HUVECs was demonstrated in a dose- and time-dependent manner. Based on the findings of RNA-sequencing (RNA-seq), enrichment of many biological processes associated with cell cycle and response to stimulus occurred. More importantly, ferroptosis was highlighted in the bioinformatic analysis of both endothelial cells. The levels of intracellular Fe 2+, MDA, and ROS were significantly increased following PA exposure while GSH was decreased, suggesting excessive iron accumulation, development of lipid peroxidation, and imbalanced redox homeostasis. Mechanistically, PA decreased the protein expression levels of GPX4 and SLC7A11 in endothelial cells, both of which played crucial roles in ferroptotic cell death. Clinical Translation: This study suggests that ferroptosis may be a useful target for novel therapeutic interventions for endothelial dysfunction and cell death in vascular diseases such as erectile dysfunction. Strengths and Limitations: In this study, we found that ferroptosis could participate in PA-induced endothelial dysfunction and cell death. A limitation of the study is that it did not shed light on the overall mechanisms of this process. Therefore, further research on the intricate networks of regulating ferroptosis is needed. Conclusion: Overall, the occurrence of ferroptosis was demonstrated in the PA-treated HUVECs and RCCECs in this study.